CUSTOMER PROTECTION AGAINST BANKING SERVICES AND CIMB NIAGA CELLPHONE ACCOUNT PAYMENT SYSTEM - Sendidevi, Ida Ayu Wayan Meryawira (Jurnal IUS (Kajian Hukum dan Keadilan), 2015)
Legal relation between parties in the cellphone account administration based on the valid Legal provision. There are no specific regulation concerning the providence of cellphone account and therefore to provide legal certainty on cellphone account its legal basic rely on existing Law and internal regulation of CIMB Niaga. Product information transparency, users safety and complain and dispute resolution effort are the things that should be fulfilled in the providence of cellphone account since they are the costumer rights which regulated in Law Number 8 of 1999 concerning customer protection.Keywords: Cellphone account, costumer protection